2018
DOI: 10.9734/ajpas/2018/v1i124495
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Programming for Statistical Inference

Abstract: The study is concerned with the transforming theoretical Mathematical models into applied Mathematical programming models that are easy to handle and use. These Mathematical programming models can be applied and used in statistical inference, which used in many applied fields, for example, quality control and its application. The aim of this paper is to suggest two mathematical programming models for hypotheses tests, which make a balance between the high power (1-β), and the probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Both acceptance sampling applications have the basic purpose of classifying a lot as accepted or rejected, given the quality levels required for it [4]. This paper used the goal programming technique to convert the mathematical programming models are going to be introduced by Elrefaey et al [5] to nonlinear goal programming models. This paper also concerned with applying the mathematical programming presented by Elrefaey et al [5] and the suggested nonlinear goal programming models, which determine the producer's risk (α), consumer's risk (β) and acceptance level (c) simultaneously.…”
Section: Methods Articlementioning
confidence: 99%
See 4 more Smart Citations
“…Both acceptance sampling applications have the basic purpose of classifying a lot as accepted or rejected, given the quality levels required for it [4]. This paper used the goal programming technique to convert the mathematical programming models are going to be introduced by Elrefaey et al [5] to nonlinear goal programming models. This paper also concerned with applying the mathematical programming presented by Elrefaey et al [5] and the suggested nonlinear goal programming models, which determine the producer's risk (α), consumer's risk (β) and acceptance level (c) simultaneously.…”
Section: Methods Articlementioning
confidence: 99%
“…This paper used the goal programming technique to convert the mathematical programming models are going to be introduced by Elrefaey et al [5] to nonlinear goal programming models. This paper also concerned with applying the mathematical programming presented by Elrefaey et al [5] and the suggested nonlinear goal programming models, which determine the producer's risk (α), consumer's risk (β) and acceptance level (c) simultaneously. Real quality control data are used to evaluate the performance of the suggested models, which is used to determine the producer's risk α, consumer's risk β and acceptance level (c).…”
Section: Methods Articlementioning
confidence: 99%
See 3 more Smart Citations